Unraveling the protein kinase C/NDRG1 signaling network in breast cancer - C. Saponaro; M. Damato; E. Stanca; S. Aboulouard; F. A. Zito; S. De Summa; D. Traversa; L. Schirosi; S. Bravaccini; F. Pirini; E. Fonzi; M. Tebaldi; et al. (Cell & Bioscience)
Abstract N-myc downstream-regulated gene 1 (NDRG1) is a member of the NDRG family of intracellular proteins and plays a central role in a wide range of biological processes including stress response, differentiation, and metabolism. The overexpression of NDRG1 is an indicator of poor prognosis in various types of cancer. Here, we found that NDRG1 is an independent prognostic marker of poor outcome in breast cancer (BC). Analysis of the TCGA dataset showed a significant positive correlation between NDRG1 and PRKCA expression, suggesting a mechanistic role of protein kinase C (PKC) in the regulation of NDRG1. We then assessed the hypothesis that PKC might modulate the activity of NDRG1, and observed that different acute stress conditions converging on PKC activation lead to enhanced NDRG1 expression. This mechanism was found to be specific for NDRG1 as the expression of other NDRG members was not affected. Moreover, CRISPR-based inhibition of NDRG1 expression was obtained in a BC cell line, and showed that this protein is a key driver of BC cell invasion through the Rho-associated coiled-coil containing protein kinase 1 (ROCK1)/phosphorylated cofilin pathway that regulates stress fiber assembly, and the modulation of extracellular matrix reorganization related genes. Together, our findings highlight the potential of NDRG1 as a new BC biomarker and uncover a novel mechanism of regulation of NDRG1 expression that might lead to innovative therapeutic strategies.